Multiple antigen-engineered DC vaccines with or without IFNα to promote antitumor immunity in melanoma. Issue 1 (24th April 2019) - Butterfield, Lisa H.; Vujanovic, Lazar; Santos, Patricia M.; Maurer, Deena M.; Gambotto, Andrea; Lohr, Joel; Li, Chunlei; Waldman, Jacob; Chandran, Uma; Lin, Yan; Lin, Huang; Tawbi, Hussein A.; et al.
Abstract : Background: Cancer vaccines are designed to promote systemic antitumor immunity and tumor eradication. Cancer vaccination may be more efficacious in combination with additional interventions that may build on or amplify their effects. Methods: Based on our previous clinical and in vitro studies, we designed an antigen-engineered DC vaccine trial to promote a polyclonal CD8 + and CD4 + T cell response against three shared melanoma antigens. The 35 vaccine recipients were then randomized to receive one month of high-dose IFNα or observation. Results: The resulting clinical outcomes were 2 partial responses, 8 stable disease and 14 progressive disease among patients with measurable disease using RECIST 1.1, and, of 11 surgically treated patients with no evidence of disease (NED), 4 remain NED at a median follow-up of 3 years. The majority of vaccinated patients showed an increase in vaccine antigen-specific CD8 + and CD4 + T cell responses. The addition of IFNα did not appear to improve immune or clinical responses in this trial. Examination of the DC vaccine profiles showed that IL-12p70 secretion did not correlate with immune or clinical responses. In depth immune biomarker studies support the importance of circulating Treg and MDSC for development of antigen-specific T cell responses, and of circulating CD8 + and CD4 + T cell subsets in clinical responses. Conclusions: DC vaccines are a safe and reliable platform for promoting antitumor immunity. This combination with one month of high dose IFNα did not improve outcomes. Immune biomarker analysis in the blood identified several predictive and prognostic biomarkers for further analysis, including MDSC. Trial registration: NCT01622933 .